2017
DOI: 10.1016/j.arr.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural neuroimaging in preclinical dementia: From microstructural deficits and grey matter atrophy to macroscale connectomic changes

Abstract: The last decade has witnessed a proliferation of neuroimaging studies characterising brain changes associated with Alzheimer's disease (AD), where both widespread atrophy and 'signature' brain regions have been implicated. In parallel, a prolonged latency period has been established in AD, with abnormal cerebral changes beginning many years before symptom onset. This raises the possibility of early therapeutic intervention, even before symptoms, when treatments could have the greatest effect on disease-course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 164 publications
(246 reference statements)
3
41
0
Order By: Relevance
“…Interestingly, Compta et al. observed a reverse relationship in the PD-D group, where increased CSF α -synuclein was associated with atrophy in the parahippocampal gyrus and precuneus, both of which are commonly implicated in preclinical and established stages of dementia (Mak et al., 2017, Villemagne and Chételat, 2016). However, the correlations did not persist after adjusting for CSF tau, suggesting that any effects of CSF α -synuclein may be mediated through tau (Compta et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Compta et al. observed a reverse relationship in the PD-D group, where increased CSF α -synuclein was associated with atrophy in the parahippocampal gyrus and precuneus, both of which are commonly implicated in preclinical and established stages of dementia (Mak et al., 2017, Villemagne and Chételat, 2016). However, the correlations did not persist after adjusting for CSF tau, suggesting that any effects of CSF α -synuclein may be mediated through tau (Compta et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a significant association between accelerated DNAm age (based on the Hannum epigenetic age clock) and two MRI measures (Supplementary have been associated with aging and symptomatic neurodegeneration and could be chance findings. Alternatively, epigenetic aging associated with increased FA and decreased MD could be linked with comparable findings in presymptomatic carriers of familial AD mutations, where it has been suggested that such findings could reflect earlier axonal insults in the pathway toward subsequent neurodegeneration such as neuroinflammatory changes leading to neuronal and glial swelling [42,43]. Nevertheless most studies indicated no change or decreased FA and increased MD in preclinical familial AD [42].…”
Section: Accelerated Blood Dnam Age Is Associated With Mri Alterationsmentioning
confidence: 95%
“…Alternatively, epigenetic aging associated with increased FA and decreased MD could be linked with comparable findings in presymptomatic carriers of familial AD mutations, where it has been suggested that such findings could reflect earlier axonal insults in the pathway toward subsequent neurodegeneration such as neuroinflammatory changes leading to neuronal and glial swelling [42,43]. Nevertheless most studies indicated no change or decreased FA and increased MD in preclinical familial AD [42]. No associations were observed between the Horvath epigenetic clock and any of the imaging variables tested and neither of the epigenetic clocks were associated with cognitive function or presence of cognitive impairment.…”
Section: Accelerated Blood Dnam Age Is Associated With Mri Alterationsmentioning
confidence: 96%
“…Brain damage associated to AD starts decades before the symptomatic onset and clinical diagnose, which has led to consider AD as a continuum (Dubois et al, 2016;Jack et al, 2018). In this line, studies performed on AD risk population such as carriers of apolipoprotein E (APOE)-ε4 or rs405509 alleles have detected brain differences between these subjects and control subjects in elderly Reiter et al, 2017;Shu et al, 2015) and middle-age healthy population (Cacciaglia et al, 2018;Habib et al, 2017;Mak et al, 2017;ten Kate et al, 2016).…”
Section: Introductionmentioning
confidence: 99%